2022
DOI: 10.1155/2022/6077748
|View full text |Cite
|
Sign up to set email alerts
|

Optical Resolution Photoacoustic Microscopy Imaging in the Detection of Early Oral Cancer under Image Reconstruction Algorithm

Abstract: This research was intended to explore the application value of photoacoustic imaging technology based on image intelligent iterative reconstruction algorithm in the detection and diagnosis of early oral cancer. An iterative algorithm model was constructed and systematically analyzed. The algorithm was used to debug the detection of B-scan images on the diameter of the imaging area. The results showed that the sensitivity of line-focused ultrasound detector was 86.72% and the specificity was 80.79%, while the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Evaluating parameters such as blood flow and oxygenation levels can offer valuable information, leading to a more comprehensive understanding of oral pathologies and potentially improved diagnosis of oral diseases. Additionally, while existing research has demonstrated the advantages of microscopy and tomography-based PA in detecting and characterizing early-stage oral pathologies, none of these studies have extended to dual-modal configurations (Li and Dewhurst, 2016;Zhang and Wang, 2022). Integrating the PA system with ultrasonic modality can potentially enhance the identification of subtle abnormalities and lesions in the early stages, providing a more effective diagnostic approach.…”
Section: Figure 12mentioning
confidence: 99%
“…Evaluating parameters such as blood flow and oxygenation levels can offer valuable information, leading to a more comprehensive understanding of oral pathologies and potentially improved diagnosis of oral diseases. Additionally, while existing research has demonstrated the advantages of microscopy and tomography-based PA in detecting and characterizing early-stage oral pathologies, none of these studies have extended to dual-modal configurations (Li and Dewhurst, 2016;Zhang and Wang, 2022). Integrating the PA system with ultrasonic modality can potentially enhance the identification of subtle abnormalities and lesions in the early stages, providing a more effective diagnostic approach.…”
Section: Figure 12mentioning
confidence: 99%